The Strategies for Developing the Concept of Multicultural Education in Islamic Boarding School (Pesantren) and Diniyyah - Minarni Minarni; Alfauzan Amin; Zubaedi Zubaedi; Ismail Ismail (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: The Strategies for Developing the Concept of Multicultural Education in Islamic Boarding School (Pesantren) and DiniyyahObjective: This study aims to examine the strategy of developing the concept of multicultural education in pesantren and diniyyah, focusing on understanding, tolerance, and respect for cultural and religious diversity among santri. Methods: This research was conducted in 2023 using a qualitative approach. The research subjects included pesantren managers, educators, and santri. Data was collected through in-depth interviews, and qualitative data analysis used a thematic approach to identify key themes and insights. Results: This study found that the development of multicultural education in pesantren and diniyyah has great potential for future progress. Conclusion: Multicultural education in pesantren and diniyyah can play an important role in building social cohesion, as it provides santri with the skills and perspectives needed to interact respectfully in a diverse society. Contribution: This research enriches the literature on multicultural education in Indonesia, particularly in pesantren and diniyyah, which have unique characteristics compared to other formal education systems.INDONESIA: Strategi Pengembangan Konsep Pendidikan Multikultural di Pesantren dan DiniyahTujuan: Penelitian ini bertujuan untuk mengkaji strategi pengembangan konsep pendidikan multikultural di pesantren dan diniyyah, dengan fokus pada pemahaman, toleransi, dan penghormatan terhadap keragaman budaya dan agama di kalangan santri. Metode: Penelitian ini dilakukan pada tahun 2023 dengan menggunakan pendekatan kualitatif. Subjek penelitian meliputi pengelola pesantren, pendidik, dan santri. Pengumpulan data dilakukan melalui wawancara mendalam, dan analisis data kualitatif menggunakan pendekatan tematik untuk mengidentifikasi tema-tema dan wawasan kunci. Hasil: Penelitian ini menemukan bahwa pengembangan pendidikan multikultural di pesantren dan diniyyah memiliki potensi besar untuk kemajuan di masa depan. Kesimpulan: Pendidikan multikultural di pesantren dan diniyyah dapat memainkan peran penting dalam membangun kohesi sosial, karena memberikan santri keterampilan dan perspektif yang dibutuhkan untuk berinteraksi dengan hormat dalam masyarakat yang beragam. Kontribusi: Penelitian ini memperkaya literatur tentang pendidikan multikultural di Indonesia, khususnya dalam konteks pesantren dan diniyyah yang memiliki karakteristik unik dibandingkan dengan sistem pendidikan formal lainnya.